(untitled) (FULafia Journal of Science and Technology, 2019)
This study investigates the significant contribution of neighbourhood factors on the choice of residential users’ locations in their decision making process within Ibadan North Local Government Area (IBNLGA) of Oyo State The research is a survey type in which the residential property users, and the property managers or agents within the three residential densities (high: Mokola, Oniyanrin, Omitowoju and Inalende-Ode Olo areas; medium: Basorun, Idi-Ape, Basorun, and Ashi areas; and low: Bodija Old and New Estates, Ikolaba Estate areas) of the selected neighbourhoods in IBNLGA; were administered structured and close-ended questionnaire to collect relevant data needed for analysis. The data were analysed using the binary logistic regression statistics (in which the dependent variable was choice of location and the variables of influence were ten neighbourhood factors) with the aid of Computer Aided Statistical Package for Social Science (SPSS) Version 16. The result of the analysis revealed that neighbourhood factors influencing users’ choice of residential location varied among the three residential neighbourhoods. At P- value 0.05 levels, the common significant factor in the choice of residential neighbourhood in all the residential densities was the rent passing. In high density neighbourhood, the most significant factor for the choice of residential location was noise level and others.